SOLUBILITY MECHANISMS OF FLUORINE IN PERALKALINE AND META-ALUMINOUS SILICATE GLASSES AND IN MELTS TO MAGMATIC TEMPERATURES - Mysen B.O.; Cody G.D.; Smith A. (My University, 2004)
Structural interaction between dissolved fluorine and silicate glass (25°C) and melt (to 1400°C) has been examined with 19F and 29Si MAS NMR and with Raman spectroscopy in the system Na2O-Al2O3-SiO2 as a function of Al2O3 content. Approximately 3 mol.% F calculated as NaF dissolved in these glasses and melts. From 19F NMR spectroscopy, four different fluoride complexes were identified. These are (1) Na-F complexes (NF), (2) Na-Al-F complexes with Al in 4-fold coordination (NAF), (3) Na-Al-F complexes with Al in 6-fold coordination with F (CF), and (4) Al-F complexes with Al in 6-fold, and possibly also 4-fold coordination (TF). The latter three types of complexes may be linked to the aluminosilicate network via Al-O-Si bridges.The abundance of sodium fluoride complexes (NF) decreases with increasing Al/(Al + Si) of the glasses and melts. The NF complexes were not detected in meta-aluminosilicate glasses and melts. The NAF, CF, and TF complexes coexist in peralkaline and meta-aluminosilicate glasses and melts.From 29Si-NMR spectra of glasses and Raman spectra of glasses and melts, the silicate structure of Al-free and Al-poor compositions becomes polymerized by dissolution of F because NF complexes scavenge network-modifying Na from the silicate. Solution of F in Al-rich peralkaline and meta-aluminous glasses and melts results in Al-F bonding and aluminosilicate depolymerization.Temperature (above that of the glass transition) affects the Qn-speciation reaction in the melts, 2Q3 ⇔ Q4 + Q2, in a manner similar to other alkali silicate and alkali aluminosilicate melts. Dissolved F at the concentration level used in this study does not affect the temperature-dependence of this speciation reaction.